Environmental Graphic Design as An Information Media for The Mecca Area Park - Zenmira, Kharisma Nanda; Kholifah, Yuli (IJESS International Journal of Education and Social Science, 2024)
The Mecca Park in Pasuruan City is a religious tourism destination with strategic potential but faces the problem of a lack of adequate visual information systems. This study aims to design a comprehensive and effective Environmental Graphic Design (EGD) as an information medium to improve the quality of visual services and tourist experiences. The research method uses a Research and Development (R&D) approach with the Sugiyono model simplified into 7 stages. The research subjects consisted of 10 respondents for the small-scale trial and 82 respondents for the large-scale trial. The design concept developed is "Islamic Heritage & Spiritual Elegance" which is in line with the religious characteristics of the destination. The EGD system includes five main components: directional signs, informational signs, regulatory signs, orientation signs, and identification signs using a black-gold-white color scheme, League Spartan and DM Sans typography, and weather-resistant Aluminum Composite Panel (ACP) material. The results of the validation test by media experts and material experts showed a score of 93% with a "very feasible" category. The trial resulted in a feasibility level of 95% on a small scale and 89.2% on a large scale, both in the "very feasible" category. The implementation of EGD has successfully addressed the visual information issues in accordance with the Regulation of the Indonesian Ministry of Tourism No. 3 of 2018, and has contributed to improving the tourist experience and developing religious tourism destinations based on religious and cultural values.